Hydrological response of Chamelia Watershed in Mahakali Basin to climate change - Pandey, Vishnu Prasad; Dhaubanjar, Sanita; Bharati, Luna; Thapa, Bhesh Raj (Elsevier, 2019)
Chamelia (catchment area = 1603 km2 ), a tributary of Mahakali, is a snow-fed watershed in Western Nepal. The watershed has 14 hydropower projects at various stages of development. This study simulated the current and future hydrological system of Chamelia using the Soil and Water Assessment Tool (SWAT). The model was calibrated for 2001–2007; validated for 2008–2013; and then applied to assess streamflow response to projected future climate scenarios. Multi-site calibration ensures that the model is capable of reproducing hydrological heterogeneity within the watershed. Current water balance above the Q120 hydrological station in the forms of precipitation, actual evapotranspiration (AET), and net water yield are 2469 mm, 381 mm and 1946 mm, respectively. Outputs of five Regional Climate Models (RCMs) under two representative concentration pathways (RCPs) for three future periods were considered for assessing climate change impacts. An ensemble of bias-corrected RCM projections showed that maximum temperature under RCP4.5 (RCP8.5) scenario for near-, mid-, and far-futures is projected to increase from the baseline by 0.9 °C (1.1 °C), 1.4 °C (2.1 °C), and 1.6 °C (3.4 °C), respectively. Minimum temperature for the same scenarios and future periods are projected to increase by 0.9 °C (1.2 °C), 1.6 °C (2.5 °C), and 2.0 °C (3.9 °C), respectively. Average annual precipitation under RCP4.5 (RCP8.5) scenario for near-, mid-, and far-futures are projected to increase by 10% (11%), 10% (15%), and 13% (15%), respectively. Based on the five RCMs considered, there is a high consensus for increase in temperature but higher uncertainty with respect to precipitations. Under these projected changes, average annual streamflow was simulated to increase gradually from the near to far future under both RCPs; for instance, by 8.2% in near-, 12.2% in mid-, and 15.0% in far-future under RCP4.5 scenarios. The results are useful for planning water infrastructure projects, in Chamelia and throughout the Mahakali basin, to ensure long-term sustainability under climate change.